Addition of rituximab to CHOP-like chemotherapy in first line treatment of primary mediastinal B-cell lymphoma - Kriegsmann, Katharina; Cremer, Martin; Kriegsmann, Mark; Ho, Anthony Dick; Witzens-Harig, Mathias (BMC cancer, 2017)
Background: The addition of rituximab (R) to CHOP (cyclophosphamide, doxorubicin, vincristine and prednisone) -like therapy has improved survival in primary mediastinal B-cell lymphoma (PMBCL) patients. However, these results were obtained in young low risk patients and a reevaluation in an unselected patient cohort is warranted. Methods: In this study, we analyzed 80 PMBCL patients treated with a CHOP-based regimen with and without rituximab. Results: In the non-rituximab cohort 10-year progression free survival (PFS) was 67% and 10-year overall survival (OS) was 72% versus a PFS of 95% and a OS of 92% in the rituximab group, PFS P = 0.001, OS P = 0.023. A subgroup PFS analysis by international prognostic index (IPI) risk revealed that all risk groups benefit from addition of rituximab to induction chemotherapy. In addition, OS probability was higher in the group of non-low risk patients who were treated with rituximab compared to those patients who did not receive rituximab (P = 0.035). In multivariate analysis, only addition of rituximab to induction chemotherapy and reaching complete remission (CR) after first line therapy had a beneficial effect on both PFS and OS, whereas IPI, age, upfront high dose (HD) chemotherapy/autologous blood stem cell transplantation (ABSCT) and rituximab maintenance had no impact on survival. Conclusions: Our data demonstrate a survival benefit in unselected PMBCL patients treated with CHOP-like induction regimen and additional rituximab independently of the IPI risk score.